Summer Workshop in Individualization of Instruction, 1970. Selected Papers - Bicknell, John E.; And Others; State Univ. of New York, Fredonia. Coll. at Fredonia ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This report briefly describes a summer workshop on individualizing instruction in which 34 teachers, instructional team leaders, and administrators participated. It lists workshop personnel and participants. The major part of the report consists of eight papers written by workshop staff. Titles are (1) "The Importance of Assessment and Behavioral Objectives in Individualizing Instruction," (2) "Overview and Meaning of Individualized Instruction," (3) "Individualization in Mathematics," (4) "Differentiated Staffing in the POISE Model," (5) "Motivational Procedures in the Individualization of Instruction," (6) "Organization in Individualization," (7) "Individually Guided Reading," (8) "Microteaching and the Minicourse--A Brief Overview of the Programs of the Far West Laboratory." (RT)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Differentiated Staffs; Individualized Instruction; Individualized Reading; Inservice Teacher Education; Institutes (Training Programs); Mathematics Instruction; Microteaching; Minicourses; Staff Role; Student Evaluation; Student Motivation; Summer Programs; Teaching Methods